Easy chemistry step-by-step master high-frequency concepts for chemistry proficiency--fast! - DeWane, Marian L. (New York McGraw-Hill Education, 2014)
Easy Chemistry Step-by-Step is based on the idea that the quickest route to learning this subject isbuilding a solid foundation in the basics. You won't find a lot of pointless discussion; instead, you get an original, step-by-step approach to mastering chemistry, with important concepts linked together by clear explanations, appropriate exercises, and helpful answers.--Publisher's description.
The elements of the periodic table -- Atomic structure and atomic mass -- Ionic compound naming and formula writing -- Covalent compound naming and formula writing -- Acid theories, naming, and formula writing -- Physical and chemical properties and changes -- Measurements and significant figures -- Density -- Formula mass, moles, and molar mass -- Percent composition -- Balancing a chemical equation -- Rules for drawing Lewis structures of molecules and ions -- An introduction to acids, bases, and salts -- Writing and naming organic compound forumlas -- Balancing oxidation-reduction reactions.
Includes index.
Keywords: Chemistry; Chemistry -- Problems, exercises, etc